2017
DOI: 10.1002/cb.1666
|View full text |Cite
|
Sign up to set email alerts
|

Consumer response to brand involved in food safety scandal: An exploratory study based on a recent scandal in India

Abstract: This paper focuses on the product-harm oriented brand crisis situation from the perspective of food safety scandal. Food safety scandals cause the deterioration of consumer confidence and thereby affect consumer food choices. However, there exists a lack of studies that examine the consumer response to a brand involved in a food safety scandal. The main research questions addressed are (a) to explicate a detailed mechanism of the consumer response towards a brand involved in food safety scandal and (b) what pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 62 publications
0
31
0
1
Order By: Relevance
“…At the same time, there were issues of food naturalness and authenticity in terms of food safety and easy-to-use feature in food distribution demanded by consumers (Yeung & Morris, 2001;Fontes et al, 2015). The perception of healthy ingredients became a marketing strategy for restoring the purchase intention and mitigated the blame among consumers (Roy, Tata, & Parsad, 2018).…”
Section: Figure 2 the Product Utility Attributes Of Feature Physiological Function Social Function Psychological Function And Product Benmentioning
confidence: 99%
“…At the same time, there were issues of food naturalness and authenticity in terms of food safety and easy-to-use feature in food distribution demanded by consumers (Yeung & Morris, 2001;Fontes et al, 2015). The perception of healthy ingredients became a marketing strategy for restoring the purchase intention and mitigated the blame among consumers (Roy, Tata, & Parsad, 2018).…”
Section: Figure 2 the Product Utility Attributes Of Feature Physiological Function Social Function Psychological Function And Product Benmentioning
confidence: 99%
“…Fueled by a lack of knowledge of production systems (Brombin et al 2019), the consequent permissive environment helped large-scale industrialization and globalization of food supply chains to emerge. This lengthening of mainstream supply chains inevitably created significant issues or externalities 4 in the market highlighted by food scandals (Barbarossa et al 2016;Liu and Ma 2016;Roy et al 2018); loss of trust (Watts et al 2005); worsening conditions for small farmers (Allaben 2020); unethical practices (Rollin 2004;Rollin 2007); or other individual reasons, such as health issues. Such an economic system assumes land, labor, and money as "elements of industry" and are subject to market mechanisms of production, sale, price signals, supply and demand, and exchange through buyer and seller (Gemici 2007).…”
Section: Transformation Of Marketplaces and Consumer Activismmentioning
confidence: 99%
“…The use of explicit governance and a varied range of certifications such as the use of Denominazione di Origine Controllate (Italy)/Appellation d'Origine Contrôlée (France) for wine, and ethical and environmental accreditations (including certificates of Organic farming practice, Fairtrade, and biodynamic methodologies), and third party certifications to establish authenticity represent this contemporary approach (Giorda 2018). However, these approaches are developed under transparency and traceability measures, and the credibility of these systems has been challenged globally due to recent high-profile food scandals (Barbarossa et al 2016;Liu and Ma 2016;Roy et al 2018). Watts et al (2005) revealed that the existence of a certificate de facto demonstrates a disembedded production 8 (Page 30 of reference), but this revelation simultaneously fails to acknowledge the fact that all supply chains are embedded to some degree in specific territories and particular social contexts (Bowen 2011).…”
Section: Meaning Of Provenance In Non-indigenous Rationalmentioning
confidence: 99%
“…The purchase, investment, regulation, and other behaviors of internal and external participants will change, influenced by incidents on food safety [ 27 ]. These changes determine the costs and benefit of food safety strategies for large and small companies in period T + 1 (the next period) and their choice of food fraud or safety investment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%